PROMOSI PENJUALAN, STORE ATMOSPHERE, DAN BRAND IMAGE BERPENGARUH TERHADAP REPURCHASE INTENTION - Prakasa Restuputra, Made Dio; Rahanatha, Gede Bayu (E-Jurnal Manajemen; Vol 9 No 8 (2020)DO - 10.24843/EJMUNUD.2020.v09.i08.p07, 2020)
Drinking coffee habit in Denpasar, creates an opportunity to attract consumers to repurchase intention. Factors that influence the occurrence of repurchase intention include sales promotions, store atmosphere, and brand image. Purpose of this study are to determine the effect of sales promotion, store atmosphere, and brand image on repurchase intention. This research is conducted on consumers Excelso Cafe products. Sample are 112 respondents with purposive sampling. Data collection is carried out by questionnaire, analyzed by multiple linear regression. Based on the results, sales promotions have a significant positive effect on repurchase intention, store atmosphere has a significant positive effect on repurchase intention, brand image has a positive and significant effect on repurchase intention. Sales promotion, store atmosphere, and a good brand image greatly affect repurchase intention. Excelso should pay more attention to sales promotions, store atmosphere, and brand image felt by consumers in order to increase repurchase intention from consumers. Keywords: sales promotion, store atmosphere, brand image, repurchase intention